Technology transfer: Challenges and prospective Arab world as a case study - Faris, Waleed Fekry; El Hawari, Yaser; Ihsan, Sany Izan; Hassan Abdalla Hashim, Aisha (2009)
In the 21st century more than ever, technology is the driving engine behind civilizations. Technology level has become an indicator of advancement and living standard. No county whatsoever can lead and prosper without owning and developing technologies locally. The first step in the take off will be to transfer the available technologies. With the huge burst of discoveries made in the last century and the vast amount of technologies developed, this age’s technology transfer is no easy task. Countries that are not in the race to own and develop their own technologies and be a part of this global scientific move are betting with their own existence. This research tries to compose fragments of what have been said about the topic, trying to understand the complexity and the seriousness of the situation in that area of the world. Starting with aiming goals, outlining broad strategies, previewing the major efforts in the field and finally try to evaluate the current situation. Arab World has been used as a case study for the work.